2010
DOI: 10.1186/1471-2180-10-94
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity at different stages of the composting process

Abstract: BackgroundComposting is an aerobic microbiological process that is facilitated by bacteria and fungi. Composting is also a method to produce fertilizer or soil conditioner. Tightened EU legislation now requires treatment of the continuously growing quantities of organic municipal waste before final disposal. However, some full-scale composting plants experience difficulties with the efficiency of biowaste degradation and with the emission of noxious odours. In this study we examine the bacterial species richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
184
2
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(226 citation statements)
references
References 48 publications
15
184
2
8
Order By: Relevance
“…However, some actinobacteria isolates in this study were thermotolerant (results not shown). Partanen et al (2010) and Sundberg et al (2011) showed a correlation between a rising pH with an increase in actinobacteria. However, Goodfellow and Williams (1983) reported that various actinobacteria are involved in all compost stages which demonstrates a wide temperature range for their growth, often with an optimum between 25 and 30°C for mesophiles and 45-55°C for thermophiles.…”
Section: Enumeration Of Mesophilic and Thermophilic Indigenous Microfmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some actinobacteria isolates in this study were thermotolerant (results not shown). Partanen et al (2010) and Sundberg et al (2011) showed a correlation between a rising pH with an increase in actinobacteria. However, Goodfellow and Williams (1983) reported that various actinobacteria are involved in all compost stages which demonstrates a wide temperature range for their growth, often with an optimum between 25 and 30°C for mesophiles and 45-55°C for thermophiles.…”
Section: Enumeration Of Mesophilic and Thermophilic Indigenous Microfmentioning
confidence: 99%
“…3a, b). Partanen et al (2010); Kurola et al (2011) demonstrated that high proportions of actinobacteria indicate good composting conditions. The results of the (PCA) run between the all identified mesophilic and thermophic microflora profile and physicochemical parameters, during co-composting, show that the actinobacteria (domain I) are inversely correlated with temperature and highly correlated with pH (case of mixture B) (Fig.…”
Section: Enumeration Of Mesophilic and Thermophilic Indigenous Microfmentioning
confidence: 99%
“…Whether in controlled laboratory settings or in waste recycling centres, Geobacillus species can become the dominant culturable bacterial taxon in composts at 60-69 u C (Blanc et al, 1997;Ronimus et al, 2003;Strom, 1985;Takaku et al, 2006). When culture-independent methods are employed, however, a richer and much more nuanced picture emerges in which Geobacillus and other thermophilic members of class Bacilli still play a part, although a numerically minor one (Martins et al, 2013;Michel et al, 2002;Partanen et al, 2010;Peters et al, 2000). Yet the prevalence of geobacilli in active, hot composts gives us a place to start in assessing the likely role of Geobacillus in the natural environment.…”
Section: Lessons From Compostmentioning
confidence: 99%
“…Thermo-tolerant and thermophilic population dominates the middle phase, producing enzymes responsible for degradation of complex organic material and temperature rises further. Concluding stage of the composting is characterized by the growth of actinomycetes and fungi that degrade the most complex organic matters under high temperature and high pH environment [11] [12]. Raw material used for composting is ligno-cellulosic biomass.…”
Section: Introductionmentioning
confidence: 99%